2002
DOI: 10.1034/j.1600-0404.2002.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

MELAS: a neuropsychological and radiological follow-up study

Abstract: We report on a patient with long standing, full-blown mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes (MELAS). In contrast to earlier publications, detailed neuropsychological assessment revealed no dementia but a pattern of distinct cognitive deficits with marked impairment of visuo-constructive and executive functions. Focal lesions and progressing atrophy mainly of the basal ganglia and the temporo-parieto-occipital area with preservation of hippocampal and entorhinal structures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 8 publications
0
18
1
1
Order By: Relevance
“…This profile is consistent with the earlier misdiagnosis of developmental dyslexia as the other areas of cognition were well preserved. In previous reports of patients with mitochondrial disorders, language function was either not reported (Lang et al, 1995;Turconi, 1999;Kauffman, 2004) or impaired in some cases (Kartsounis, 1992;Sartor, 2002;Bosbach, 2003).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…This profile is consistent with the earlier misdiagnosis of developmental dyslexia as the other areas of cognition were well preserved. In previous reports of patients with mitochondrial disorders, language function was either not reported (Lang et al, 1995;Turconi, 1999;Kauffman, 2004) or impaired in some cases (Kartsounis, 1992;Sartor, 2002;Bosbach, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…Diagnosis of mitochondrial dementia (Finsterer, 2009) was excluded. Mild and/or focal cognitive deficits were also described in previous reports of patients with mitochondrial disease (Kartsounis et al, 1992;Turconi et al, 1999;Sartor et al, 2002;Bosbach et al, 2003) and only in few reported cases mitochondrial dementia was diagnosed (Lang et al, 1995). MELAS patients are often described in the literature as those most cognitively impaired, but often they were not always diagnosed with mitochondrial dementia as they presented with focal cognitive impairments (Lang et al, 1995;Sartor et.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations